Peran Media Sosial Dalam Meningkatkan Pengetahuan Kesehatan Reproduksi Remaja - Hasiba Hasiba; Satiani Dalle; Sudin Riyadi (Barongko: Jurnal Ilmu Kesehatan, 2026)
Adolescent reproductive health is a crucial aspect of public health development. Lack of knowledge about reproductive health can increase the risk of risky sexual behavior, sexually transmitted infections, and unintended pregnancy. Social media is a widely used source of information for adolescents to acquire health knowledge. This study aims to analyze the role of social media in improving adolescent reproductive health knowledge. The study used a descriptive analytical design with a cross-sectional approach. The study sample consisted of 80 adolescents selected using a purposive sampling technique. Data were collected using a questionnaire regarding social media use and reproductive health knowledge levels. Data analysis used the chi-square test. The results showed that 70% of respondents obtained reproductive health information through social media and there was a significant relationship between social media use and adolescent reproductive health knowledge levels (p = 0.003). It was concluded that social media plays a significant role in improving adolescent reproductive health knowledge.